Students' experiences and attitudes toward a newly developed simulation-based pharmaceutical care clinical rotation: A pre-post study design - Shoroq M. Altawalbeh; Minas Al-Khatib; Basima A. Almomani; Khawla Nuseir; Belal A. Al-Husein; Tareq L. Mukattash (Elsevier, 2023)
Purpose: This study aims to evaluate Doctor of Pharmacy (PharmD) students' experience with the newly developed simulation-based pharmaceutical care (PC) rotation by evaluating their knowledge and attitudes towards PC before and after the rotation. Methods: A self-administered questionnaire was distributed to sixth year PharmD students enrolled in the clinical training rotation "Comprehensive Pharmaceutical Care" during the 2020/2021 academic semesters at Jordan University of Science and Technology's (JUST) Faculty of Pharmacy. Questionnaires were distributed before and after completing four experiential training weeks and consisted of three sections. The first section collected students' demographic details while the second and third sections evaluated students' knowledge about, and attitudes toward PC, respectively. Descriptive statistics were used to describe and compare changes in students' knowledge and attitudes pre-and post-rotation. Results: A total of 106 valid questionnaires were completed with a response rate of 99.07%. The rates of correct answers increased after the rotation with median total knowledge score increasing from 8 to 10 (out of 13, P value < 0.001). Significant improvements in students' understanding of aspects relating to the concept and process of PC, and the role of clinical pharmacist in PC provision, were shown post the simulation-based clinical rotation. Similarly, their attitudes toward performing PC were either improved or emphasized. In contrast results also revealed that specific aspects of the rotation require further refinement, such as the comprehensiveness of the PC process and responsibilities in providing PC. Conclusions: PharmD students' understanding and attitudes toward PC were either improved or emphasized after the simulation-based PC rotation. This study highlights the value of simulation as a unique instructional technique that can assist educators to develop PC competencies for pharmacy students.